2013
DOI: 10.1007/s10152-013-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

First molecular phylogeny of the subfamily Polycerinae (Mollusca, Nudibranchia, Polyceridae)

Abstract: The subfamily Polycerinae includes four genera with around 46 species described to date. This subfamily is characterized by a limaciform body, which may have simple tentacular processes on the margin of the oral veil. Phylogenetic relationships between the genera of the subfamily Polycerinae (Polyceridae) have not yet been studied, and therefore, the only available information is based on morphological descriptions. The present study reports the first phylogenetic analysis of Polycerinae based on the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The nudibranch species J. tomentosa (family Discodorididae) was chosen for outgroup taxa in the phylogenetic analyses based on the results of Palomar et al . (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nudibranch species J. tomentosa (family Discodorididae) was chosen for outgroup taxa in the phylogenetic analyses based on the results of Palomar et al . (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, 47 sequences of the cytochrome c oxidase subunit I (COI) of Polycera quadrilineata and other Polyceridae taxa, representing a total of 17 species, together with the outgroup species Jorunna tomentosa (Cuvier, 1804) were obtained from GenBank and BOLD databases ( Table 1). The nudibranch species J. tomentosa (family Discodorididae) was chosen for outgroup taxa in the phylogenetic analyses based on the results of Palomar et al (2014).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Although the monophyly of the subfamily Polycerinae was supported by molecular data (Palomar et al, 2014) confirming its phylogenetic identity as revealed by morphological studies (Alder and Hancock, 1845;Odhner, 1941), unfortunately, the relationships within Polycerinae as well as the monophyly of Polycera were never recovered (Palomar et al, 2014;Sørensen et al, 2020;Knutson and Gosliner, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…They have paired jaws, the radula has up to 20 rows of teeth; the inner lateral teeth are hooked, the second lateral teeth being larger than the first, the outer laterals being small. They have a large prostate gland, and a penis armed with spines (Gray, 1857;Pruvot-Fol, 1954;Thompson, 1975;Palomar et al, 2014;Pola et al, 2014;Sørensen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ingroup specimens, a range of outgroup sequences were selected from GenBank (Wollscheid-Lengeling et al 2001;Shields 2009;Pola and Gosliner 2010;Jung et al 2014;Palomar et al 2014;Hulett et al 2015;Mahguib and Valdés 2015;Goodheart et al 2018) (see Supplementary Table S1) along with other available sequences for Doris kerguelenensis (Wilson et al 2009(Wilson et al , 2013. This was done as a robust sister group for Dorididae, across the Nudibranchia phylogeny is not yet certain (e.g.…”
Section: Specimen Collection and Preservationmentioning
confidence: 99%